Representasi Rasisme dan Seksisme Di Jerman Dalam Pemberitaan Deutsche Welle Melalui Analisis Wacana Kritis Model Siegfried Jäger - Clarissa Winda Pramesti; Agus Ridwan (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This descriptive qualitative study aims to uncover the representation of racism and sexism in the news article "Deutschland: Rassismus und Sexismus nehmen zu" on the Deutsche Welle (DW) website. Utilizing Siegfried Jäger’s Critical Discourse Analysis (CDA), the research dissects the text through five primary dimensions: institutional framework, textual surface, linguistic-rhetorical means, ideological statements, and interpretation. The analysis of the institutional framework reveals that DW frames these issues as urgent social problems, aligning with their core values of freedom and equality. Regarding the textual surface, information is organized systematically and coherently. Through rhetorical tools and ideological statements, the study finds that specific word choices and sentence constructions depict racism and sexism as serious threats that undermine democracy and fuel national concern. Ideologically, the discourse demands a stronger state role to drive structural change. The interpretation phase confirms that racism and sexism are not merely individual issues but systemic problems weakening the social fabric. The study concludes that DW’s representation is not neutral; the media outlet actively shapes public opinion by highlighting gender inequality in the workplace and criticizing the state's inadequate response. Ultimately, DW positions itself as an observer advocating for reform and stronger protection for vulnerable groups in Germany.